POLA PERMUKIMAN TIONGHOA UDIK DI KAMPUNG CUKANGGALIH, TANGERANG - Gracia, Ruth; Khamdevi, Muhammar (Unika Santo Thomas, 2024)
Chinese kampongs are starting to face the threat of disappearance, particularly in Greater Tangerang. The Chinese Farmers settlement in Kampung Cukanggalih holds significant cultural importance that needs to be preserved, including its historical, aesthetic, scientific, and social values. Therefore, this study was conducted to understand the settlement pattern of Chinese Farmers in Kampung Cukanggalih as part of documentation efforts. This research employs a qualitative-descriptive method. The results indicate that the building patterns are centered around an open space in the middle of the settlement, following Feng Shui principles. The orientation of the houses follows Feng Shui rules based on each resident's hopes, the circulation pattern combines radial and linear with collective system linkage, viharas and temples as markers of access to enter the village, and the characteristics of the Chinese Farmers houses and its landscape strongly define the kampong's identity.